Stevia Local Tawangmangu Generation M1 Result of Oryzalin Treatment - Dian Susanti; Parjanto Parjanto; Sari Haryanti (Jurnal Biodjati, 2024)
Stevia rebaudiana Bert. (Stevia) is used in the commercial and health industries because of its steviol glycosides (stevioside, rebaudioside A, rebaudioside C) and flavonoids. Polyploidy induction of stevia plants using oryzalin was held to increase the diversity and produce superior varieties. This research aims to obtain stevia diversity with different characteristics from its diploid. The Tawangmangu variety of stevia seedlings was experimentally designed using a completely random design. Nine combinations of oryzalin concentrations (1.5, 2.5, and 3.5μM) and immersion times (4, 6, and 8 hours) treatments were applied to 15 stevia seedlings each. Stevia without treatment was used as a control. Treatments were applied directly to the shoots on the second internode from the tip. Observations on target shoots included the number of survivors, morphological variables (height, number of internodes, internode length, leaf size, leaf thickness, stem diameter, and leaf color), stomata, and plant ploidy level. Data analysis on the number of live plants used frequency and descriptively. Morphological data consisting of plant height, number of shoots, number of internodes, internode length, leaf length, leaf width, leaf thickness, and stem diameter were analyzed using boxplot graphs and descriptive to describe the diversity of M1 stevia treatment results. Leaf color and stomata were analyzed descriptively. The results showed that up to 3.5μM concentrations of oryzalin and 6 hours of immersion time were safe to use as a mutation agent with above 67% survival rate. Various oryzalin treatments of Tawangmangu stevia varieties yielded polyploidy morphological growth indications in height, number of internodes, internode length, stem diameter, leaf size, leaf thickness, leaf color, stomata, and stem diameter. In addition, there are growth variations such as chimeras, rosettes, and leaf splitting. However, further flow cytometry tests showed that oryzalin concentration and immersion duration directly on the vegetative material did not produce polyploid stevia individuals.